Production and Properties of Alternative Fuels from the Pyrolysis of Used Plastic Bags and Buckets - Ida Bagus Alit; I Made Mara (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2026)
This study aims to examine the properties of liquid fuel produced from the pyrolysis of two types of plastic waste: plastic buckets and plastic bags. The pyrolysis method is used to convert plastic waste into fuel oil (BBM) at high temperatures in the absence of oxygen. Experimental results show that 0.736 to 0.863 kg of fuel oil can be obtained from 1 kg of raw material. The color of the resulting fuel oil is influenced by the original color of the plastic material, indicating an effect of the chemical composition on the final product. Physical analysis shows that the density and kinematic viscosity of the fuel oil from plastic buckets are slightly lower than those of the fuel oil from plastic bags. However, both have values close to the characteristics of gasoline. The calorific value of the fuel oil from both types of plastic waste is still lower than that of gasoline and diesel, but sufficiently high for use as an alternative fuel. The ash and lead content in the pyrolysis fuel also remains below the maximum allowable limits for motor vehicle use. Thus, the fuel produced from plastic waste pyrolysis has the potential to be an environmentally friendly and sustainable alternative energy source.